STRATEGI MENINGKATKAN KUNJUNGAN WISATAWAN DI HOTEL PUSAKO BUKITTINGGI - Tiara Rahmadhani Sanjaya; Ilham Illahi (Komunitas Manajemen Kompetitif, 2026)
The issues facing the Pusako Bukittinggi Hotel, which is seeing a decline in the number of tourists wishing to stay overnight or stay because of the hotel's inability to control internal and external factors that may result in fewer visits from both domestic and foreign visitors, are the driving force behind this study. This study's goal is to outline the analysis of strategies for boosting Pusako Bukittinggi Hotel visits. The purpose of this study is to examine the tactics used by the Pusako Bukittinggi Hotel to boost tourism. Effective strategic measures are required to draw and keep tourists in the face of the hotel industry's fiercely competitive environment. This study employs a qualitative research methodology, gathering data via observations, interviews, and documentation. According to the study's findings, the Pusako Bukittinggi Hotel employs a number of key tactics, such as enhancing the quality of its services, collaborating with travel agencies to promote its brand online, and creating amenities that enhance visitor comfort. There are still issues, like a lack of creative promotions and price competition from other hotels, even though a number of tactics have improved the number of visits. Consequently, it is advised that the Pusako Bukittinggi's management Oral and written information about the subject of the research being studied describing a situation about the Analysis of Strategies to Increase Tourist Visits at Bukittinggi Hotels to Increase Tourist Visits is produced by the hotel, which continues to assess and innovate strategies to maintain and increase the level of visits